Effect of increasing urea level in protein supplements on performance by beef cows consuming low-quality tallgrass-prairie forage - Kster, H.H.; Cochran, R.C.; Vanzant, E.S.; Olson, K. C.; Jones, Timothy J.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Ninety pregnant Angus Hereford cows consuming low-quality, tallgrass-prairie hay were used to evaluate the influence of changing the amount of supplemental degradable intake protein (DIP) derived from urea on body weight and body condition changes, pregnancy rate, and calf performance. Supplemental treatment groups were: 0, 20, and 40% of the supplemental DIP from urea. Supplements were formulated to contain 30% CP . When sufficient DIP was offered to prepartum cows to maximize DOMI, urea could replace up to 40% of the DIP in a high-protein (30%) supplement without causing problems of supplement palatability. However, trends in body weight and condition indicate that performance may be enhanced if the percent of supplemental DIP from urea is less than 40%.
Keywords: Beef; Cows; Forage; Nonprotein nitrogen; Intake; Digestibility